2022
DOI: 10.3389/fcimb.2022.1004339
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T cell repertoires by commensal microbiota

Abstract: The gut microbiota plays an important role in regulating the host immune systems. It is well established that various commensal microbial species can induce the differentiation of CD4+ T helper subsets such as Foxp3+ regulatory T (Treg) cells and Th17 cells in antigen-dependent manner. The ability of certain microbial species to induce either Treg cells or Th17 cells is often linked to the altered susceptibility to certain immune disorders that are provoked by aberrant T cell response against self-antigens. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…coli in the gut and an inflammatory response at other mucosal surfaces, suggesting that there is a T cell memory of microbial species that is tissue specific. This result also indicates that the microbiome educates T cells in a tissue-specific manner ( 17 ). Moreover, these observations also suggest that a majority of T cells take up long-term residence in the gut ( 17 ).…”
Section: Gut Microbiome and The Immune Systemmentioning
confidence: 87%
See 1 more Smart Citation
“…coli in the gut and an inflammatory response at other mucosal surfaces, suggesting that there is a T cell memory of microbial species that is tissue specific. This result also indicates that the microbiome educates T cells in a tissue-specific manner ( 17 ). Moreover, these observations also suggest that a majority of T cells take up long-term residence in the gut ( 17 ).…”
Section: Gut Microbiome and The Immune Systemmentioning
confidence: 87%
“…This result also indicates that the microbiome educates T cells in a tissue-specific manner ( 17 ). Moreover, these observations also suggest that a majority of T cells take up long-term residence in the gut ( 17 ). Changes to the microbiota, such as by fecal transplantation or antibiotic treatment, lead initially to the formation of proinflammatory T cells in some instances, and then most likely to the formation of long-term memory T cells.…”
Section: Gut Microbiome and The Immune Systemmentioning
confidence: 87%
“…As a response, the immunological repertoire can be created at different molecular levels from TCRs ( 142 ). The microbiota of a host is a complex community of microbial species that can form tissue-specific T-cell responses in mucosal tissues such as the respiratory tract, gastrointestinal tract, and urogenital tract and can induce CD4 + T cells to differentiate into various T helper cell subtypes, such as peripheral Foxp3 + Treg and Th17 cells in the gut ( 143 ). Early in life, the gut microbiota controls the location of innate lymphoid cells that express the transcription factor Promyelocytic Leukemia Zinc Finger (PLZF) in the thymus.…”
Section: The Impact Of Gut Microbiota On Tumor Immunitymentioning
confidence: 99%
“…pTreg cells develop in response to antigens derived from gut microbiota and food and are predominant in the intestinal tissues. Many studies have indicated that pTreg cells are critical for immune tolerance against these antigens [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%